Peran Aplikasi Presensi ASN dalam Meningkatkan Disiplin Kerja Pegawai di Kantor Camat Buay Pemaca Kabupaten Ogan Komering Ulu Selatan (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the effect of the use of a civil servant attendance application on employee work discipline at the Buay Pemaca Sub-district Office, Ogan Komering Ulu Regency. The study used a qualitative approach with data collection through in-depth interviews, observation, and documentation. Data analysis was conducted using thematic analysis techniques that include data reduction, data presentation, and inductive conclusion drawing to identify patterns of change in work discipline after the implementation of the attendance application. The results of the study indicate that the implementation of a digital-based attendance application has a direct impact on improving civil servant work discipline, especially in aspects of attendance and punctuality in coming to work. The online attendance system integrated with the national personnel system encourages increased employee compliance because attendance is recorded in real time and is difficult to manipulate. Although technical obstacles such as dependence on the internet network and electricity supply are still encountered, these findings indicate that the use of the attendance application contributes positively to strengthening supervision and forming a more disciplined work culture, in accordance with the objectives of the study.